PS5:104 Lymphopenia in systemic lupus erythematosus – a retrospective analysis from unidade imunologia clinica (centro hospitalar e universitÁrio do porto). (21st March 2018) - Fonseca, T; Marinho, A; Vasconcelos, C; Farinha, F
Abstract : Systemic Lupus Erythematosus (SLE) has immune dysregulation, with lymphopenia being one of the most frequent clinical findings, namely the CD4 T cells. It has been associated not only to higher risk of infections, but also to disease activity and risk of flares. The authors pretended to describe the prevalence of lymphopenia in SLE in a major centre of Immunology in Portugal. A retrospective analysis on the SLE patients was performed, with a longitudinal description of the subpopulations of lymphocytes, relating it with disease activity, organ involved, therapeutics and major infections. The sample had 48 patients, mainly constituted by females (85, 4%), median age of 43 y. 62.5% had lymphopenia in the diagnosis. At the time of the most recent peripheral blood flow citometry 66, 7% of the sample had lymphopenia, with different values of cytopenia according to lymphocytes subpopulations – T CD4: 77, 4%; T CD8: 75%; B: 83, 3%; NK: 91, 7%. Severe T CD4 lymphopenia (below 200 uL) was present in 8, 3% of the sample. 18, 8% had severe flares (SLEDAI Index) and 90% of these had low T CD4 counts (below 700 uL). The majority of patients with T CD4 under 200 uL were on severe flare. Higher frequency of corticosteroids and immunosuppressors, namely cyclophosphamide (12, 5%) was observed on the patients. 17 patients of the sample had sequential citometry analysis and a correlation between lymphopenia and activity has not observed. 17 cumulative infections were described, the majority (70, 6%) with lymphopenia. Although opportunistic infections (pulmonary aspergilosis, PML due to JC virus) were mainly seen on patients with T CD4 under 200 uL it was not mandatory this condition on this sample – cryptococcal meningitis was described on a patient with 300 uL T CD4. Lymphopenia was present in the majority of active lupus and T CD4 seems to correlate with severe flare. Lymphopenia seems to be a bystander on the evolution of the disease. Despite rare, unpredictable infections can appear on patients with T CD4 counts superior to 200 uL.